ANALISIS GELOMBANG AKUSTIK TERHADAP PENGARUH TEKANAN CASING DAN GAS HETEROGEN UNTUK MENENTUKAN KEDALAMAN LIQUID LEVEL SUMUR MINYAK MENGGUNAKAN DATA SONOLOG - Suhardi '; Usman Malik; Riad Syech (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A research has been done in analyzing an acoustic wave and its effect to casing pressure and gas flow at annulus in order to determine liquid level depth of oil well. The research used an  experiment method  using  sonolog  type  remote fire gas gun  with  its  sound wave frequency  between  30 Hz  –  60 Hz.  Data were  taken from three oil wells that are managed  by  the  Unit of business Pertamina EP Lirik. Each  well was measured  five times  at different time.  The  data obtained were analyzed  by  Total Well Management (TWM) software. They were acoustic velocity, casing pressure, and gas flow. The value of acoustic velocity  shown by  TWM  sometimes  didn’t match to the  real condition including the data of  determined  liquid level depth.  New value of  acoustic  velocity had been gotten  using  multiple regression linear  equation. Time  travel  of  wave  was measured using Down Hole Marker  at TWM.  Result of calculation of  acoustic velocity based on  measured data  for well LS-031 at November 24th 2011 was 397,7138 m/s,  for well LS-105 measured at March 13th 2010 was 359,6792 m/s, for well LS-105 measured at November 25th was 356,17 m/s. Results  of calculation  of liquid level depth for well LS-031 was 249,9634 m, for well LS-105  was 261,23 m,  and  for well LS-097 was 246,96 m.